2016
DOI: 10.5028/jatm.v8i2.558
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in-Flight Measured and Computed Aeroelastic Damping: Modal Identification Procedures and Modeling Approaches

Abstract: AbstrAct:The Operational Modal Analysis technique is a methodology very often applied for the identification of dynamic systems when the input signal is unknown. The applied methodology is based on a technique to estimate the Frequency Response Functions and extract the modal parameters using only the structural dynamic response data, without assuming the knowledge of the excitation forces. Such approach is an adequate way for measuring the aircraft aeroelastic response due to random input, like atmospheric tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…There is some evidence that the use of the potential theory generally leads to conservative damping ratios, and thus to conservative flutter velocities, which are attributed to conservative aerodynamic damping calculations: for example, Smith et al [40] indicated that "divergence and possibly flutter speeds predicted by lower-order aerodynamics may be overly conservative" and that "the utilization of linear aerodynamic models may cause overly conservative predictions in divergence and flutter speed." This tendency was observed also for higher velocities (Mach 0.85) by Follador et al [41] using ZAERO; the authors found aerodynamic damping ratios for the first wing bending mode up to 40% lower when compared to the damping ratios calculated from flight-test data. All thise evidence points to limitations of the potential theory to model the aerodynamic damping.…”
Section: Damping Ratiomentioning
confidence: 54%
“…There is some evidence that the use of the potential theory generally leads to conservative damping ratios, and thus to conservative flutter velocities, which are attributed to conservative aerodynamic damping calculations: for example, Smith et al [40] indicated that "divergence and possibly flutter speeds predicted by lower-order aerodynamics may be overly conservative" and that "the utilization of linear aerodynamic models may cause overly conservative predictions in divergence and flutter speed." This tendency was observed also for higher velocities (Mach 0.85) by Follador et al [41] using ZAERO; the authors found aerodynamic damping ratios for the first wing bending mode up to 40% lower when compared to the damping ratios calculated from flight-test data. All thise evidence points to limitations of the potential theory to model the aerodynamic damping.…”
Section: Damping Ratiomentioning
confidence: 54%
“…The damping of the two modes of flutter (bending and torsion) was theoretically analyzed with a frequency domain technique that is described in [21]. Figure 11 shows a plot of the damping factor for the two modes as a function of airspeed.…”
Section: Damping As a Function Of Airspeedmentioning
confidence: 99%
“…Normal modes analysis is one of part of the dynamic parameter for understanding the sensitivity of aeroelastic stability behavior [1]. Aeroelasticity phenomenon in-volve the study of the interaction between aerodynamic, elastic forces and inertial [2].…”
Section: Introductionmentioning
confidence: 99%